Do rol não taxativo do agravo de instrumento no Novo Código de Processo Civil - Müller, Ana Cláudia Rodrigues (2016)
The Code of Civil Procedure of 2015 established an exhaustive system on judicial review. This legislative option is new in Brazilian law, because it seems that the intention of the legislator was to limit the appropriateness of this type of appeal, leaving the decisions not reached by the article 1,015 of the 2015 Code of Civil Procedure free of estoppel to be repeated in primary appeal or the appeal counterarguments. It appears that the latest legislative reforms have been implemented to reduce the large amount of resources that crowd and clutter up the courts; therefore, it is the restriction on the interlocutory appeal. Such change brings major changes in the procedural world, which deserve to be addressed by pointing out its controversial points of disagreement in the legal community. The question that arises is the following: the list of Article 1015 is really exhaustive or would be an exemplary list? The interlocutory decisions which are not included in this list can be object of judicial review? Can the list be interpreted on an ampliative form? Would not such an interpretation be honoring principles such as economy and procedural effectiveness and foster the achievement of a more useful result and qualitatively high process, avoiding serious procedural losses? These questions are important because, although the legislator has tried to protect all situations that could cause immediate harm to the parties or third parties, it is noticeable that some situations not reached by said legal provision can cause not only loss, but also, if appreciable only on the occasion of the future appeal, delaying the processing of the process and colliding with one of the essential objectives of the new code, which is to give the highest possible rate of useful results to civil procedure. It is important to point out that for interlocutory decisions always reserved the examination of procedural issues, which of solution depends on the validity of subsequent acts. So whenever postponing the analysis of an incidental matter, assumes the risk of a future nullity, which tends to contaminate many following acts. Important to highlight that the system contains structural incoherence, because it limits the immediate possibility to appeal of judicial review in first degree of jurisdiction (artigo 1015), but allows unrestricted the possibility to appeal the interlocutory judgment given by the rapporteur, especially in the competence of processes originating in the courts (artigo 1021). Therefore, it appears that sensitive subjects to the development of appropriate and useful process would have logically and necessarily immediate appreciation, as soon as the decision emerged, in order to organize the procedural march on a technically correct manner